Danxiaorchis yangii sp. nov. (Orchidaceae: Epidendroideae), the second species of Danxiaorchis - Yang, Boyun; Xiao, Shihe; Jiang, Yawen; Luo, Huolin; Xiong, Dongjin; Zhai, Junwen; Li, Bo (Phytotaxa, 2017)
Danxiaorchis yangii (Calypsoinae, Epidendreae, Epidendroideae), a holomycotrophic new species from Jinggangshan National Nature Reserve, western Jiangxi, eastern of China, is here illustrated and described based on both morphological and phylogenetic evidences. The new species can be easily distinguished from D. singchiana by its much smaller flowers and larger Y-shaped callus adaxially bearing a additional obovoid appendage, and by its four pollinia narrowly elliptic in shape and equal in size.